REFORMULASI KEBIJAKAN DIVERSI TERHADAP SELURUH TINDAK PIDANA YANG DILAKUKAN OLEH ANAK - Lin Yan Che; Ade Adhari (Jurnal Hukum Adigama, 2021)
The juvenile criminal justice system is required to apply a restorative justice approach in accordance with article 5 paragraph (1) of the Juvenile Criminal Justice System Law. One of the processes of restorative justice is diversion. Diversion is the settlement of child cases from the criminal justice process to the criminal justice process. The problem faced in writing this thesis is how is the formulation policiy for the application of diversion to all criminal acts committed by children? The research method used in writing this thesis is normative legal research. The results of the study indicate that the diversion applied in the Juvenile Criminal Justice System Act has not been fully applied to all types of crimes committed by children. Diversion in the Juvenile Criminal Justice System Law can be carried out in the event that the crime committed is punishable by a sentence of less than 7 (seven) years in prison and is not a crime. Children who commit crimes punishable by imprisonment for more than 7 years do not get the opportunity to diversify so that the application of diversion that uses criminal threats under 7 years creates problems with the principles that are best for children and nondiscrimination. This is because the diversion arrangement in Indonesia is different from countries such as the Philippines, Ireland, Thailand and South Africa in that there is no requirement to face the threat of imprisonment which causes children to lose their right to diversion. The four countries have provided appropriate protection for children to achieve the welfare and best interests of children in accordance with the general principles contained in the Convention on the Rights of the Child